Analysing the challenges associated with infrastructural project execution in the Awutu Senya District Assembly - Odei Akrofi, Richard (2021)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirement for the Award Degree of Master of Science in Project Management